Imposing Corporate Death Penalty In Indonesia: A Discourse On Penalisation, Corporate Culture, And Deferred Prosecution Agreement - Alfons Zakaria; Abdul Madjid; Bambang Sugiri; Sihabudin; Fareed Mohd Hassan (Fakultas Hukum Universitas Udayana, 2025)
Indexed by Scopus